The English Trade-Unions - Cummings, Edward (Quarterly Journal of Economics, 1889)
Journal Article The English Trades-unions Get access Edward Cummings Edward Cummings Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 3, Issue 4, July 1889, Pages 403–435, https://doi.org/10.2307/1879641 Published: 01 July 1889